Langugage problems of post-soviet Korean people in Kazakhstan (Journal of Philosophy Culture and Political Science, 2018)
This study attempts to reveal the language conflicts of Post-Soviet Koreans in Kazakhstan to adapt to citizens of a new independent country which strongly drives to build a nation-state. What Koreans in Kazakhstan cannot speak the state language is regarded as having no basic condition to become a citizen of a renewed country and is being marginalized from the public domain. Koreans has a deep-seated dichotomous boundary of self – language and other language and shows passive practice and contradictory attitude for the duty of national language. Sustaining a linguistic identity through Koreans’ linguistic conflicts is not a free and simple choice but a complicated struggle and a political process between subject and power intersecting the subject’s past experiences, memories, and the external pressures.Key words: Koreans in Kazakhstan, the pride of Soviet Koreans, dichotomy of self-language and other language.